Weather-based Agro-advisory Services in India: Current Challenges and Emerging Opportunities - R. Naseeruddin; G. Narayana Swamy; K.C. Natraj; L. Madhavi Latha; K. Lakhman; M. Vijay Sankar Babu (Archives of Current Research International, 2025)
Historically, farmers in India relied on indigenous weather knowledge and traditional practices to manage climatic risks. While these practices offered resilience, they lacked the precision needed to cope with increasing weather variability and emerging challenges such as heat waves, cyclones, and erratic rainfall. Weather-based agro-advisory services (AAS) are a basis of climate-resilient agriculture in India. With agriculture deeply intertwined with monsoon variability, these services aim to reduce weather-related risks by delivering timely and location-specific information to farmers. This paper reviews the evolution of AAS in India, examines current operational challenges, and explores future opportunities driven by technology, institutional reform and participatory approaches. The National Innovation on Climate Resilient Agriculture (NICRA) is a landmark initiative launched by the Indian Council of Agricultural Research (ICAR) in 2011 to address the challenges posed by climate variability and extreme weather events on Indian agriculture. It was noted that one of the evolving strengths of Pradhan Mantri Fasal Bima Yojana (PMFBY)lies in its increasing reliance on weather-based agrometeorological data and advisories to improve risk assessment and expedite claim processing. While weather-based agro-advisory services have certainly made strides in India, they still face significant challenges that hinder their potential to support farmers effectively. Enhanced accuracy, personalisation, and last-mile connectivity are key to making AAS more impactful and inclusive in the face of increasing climate variability.